(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
This study aims to analyze the economic potential of utilizing fish waste in the Fish Cracker Center of Sei Lekop, East Bintan District, Bintan Regency. Using a quantitative descriptive method, production data, raw material needs, and waste processing potential were analyzed to provide a clear picture of the economic aspects of the fish cracker production process and waste management. The results show that cracker production reaches 15,118 kg/month with a fish requirement of 12,300 kg/month. The fish waste produced reaches 4,735.5 kg/month, potentially producing 1,925 kg of fish meal. The cost-benefit analysis (CBA) shows that this project is financially feasible with an NPV value of Rp 452,315,070, an IRR of 28.23%, and a payback period of 4 years..